Floating Platform and Mooring Line Optimization for Wake Loss Mitigation in Offshore Wind Farms Through Wake Mixing Strategy - Guido Lazzerini; Giancarlo Troise; Domenico P. Coiro (Energies)
Floating offshore wind turbines present peculiar characteristics that make them particularly interesting for the implementation of wind farm control strategies such as wake mixing to increase the overall power production. Wake mixing is achieved by generating an unsteady cyclical load on the blades of upwind turbines to decrease the wind deficit on downwind turbines. The possibility of exploiting the yaw motion of a floating offshore wind turbine allows for amplified wake mixing or a reduction in the workload of the control mechanism. To amplify the yaw motion of the system at a selected excitation frequency, a multi-disciplinary optimization framework was developed to modify selected properties of the floating platform and mooring line configuration of the DTU 10 MW turbine on the Triple Spar platform. At the same time, operational and structural constraints were taken into account. A simulation-based approach was chosen to design a floating platform and mooring line configuration that were optimized to integrate with the new control strategy based on wake mixing in floating offshore wind farms. Modifying the floating platform spar arrangement and mooring line properties allowed us to tune the yaw natural frequency of the system in accordance with the excitation frequency of the wake control technique and amplify the yaw motion while controlling the deviations of the operational constraints and costs from the baseline configuration.